A Survey of Challenges Facing Streaming Data - Bagui, Sikha; Jin, Katie (Transactions on Engineering and Computing Sciences, 2020)
This survey performs a thorough enumeration and analysis of existing methods for data stream processing. It is a survey of the challenges facing streaming data. The challenges addressed are preprocessing of streaming data, detection and dealing with concept drifts in streaming data, data reduction in the face of data streams, approximate queries and blocking operations in streaming data.